2009
DOI: 10.3899/jrheum.080793
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of a Prognostic Score in Histological Analysis of Renal Biopsy in Patients with Lupus Nephritis

Abstract: These results demonstrate the advantage of our prognostic score compared to subclasses in predicting the renal outcome of class IV patients [University Hospital Medical Information Network (UMIN) clinical trials registry, number UMIN 000001943].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 14 publications
2
31
0
3
Order By: Relevance
“…1A). This was of great interest because crescent formation in human membranoproliferative lupus nephritis is indicative of severe glomerular injury and associated with decreased survival and adverse outcomes (1)(2)(3). Poly (I:C)-treated mice displayed significantly higher histological glomerular and interstitial scores, with crescent formation in 60% of glomeruli; crescents were not observed in glomeruli from spontaneously proteinuric mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). This was of great interest because crescent formation in human membranoproliferative lupus nephritis is indicative of severe glomerular injury and associated with decreased survival and adverse outcomes (1)(2)(3). Poly (I:C)-treated mice displayed significantly higher histological glomerular and interstitial scores, with crescent formation in 60% of glomeruli; crescents were not observed in glomeruli from spontaneously proteinuric mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mesangial and endothelial cell proliferation and leukocyte infiltration are frequent findings of active disease. Extracapillary epithelial cell proliferation, which leads to the formation of a cellular crescent, is a less-frequent finding in human lupus nephritis; however, it is characteristic of severe glomerular injury and an indicator of poor prognosis (1)(2)(3). The underlying mechanisms of crescent formation in lupus nephritis are largely unknown.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] One study done by Kim et al 11 was excluded from analysis because it reported renal flares as an outcome and did not provide data on the doubling of serum creatinine concentration or ESRD. Characteristics of the remaining eight studies are given in Table 1.…”
Section: Studies Includedmentioning
confidence: 99%
“…However, among those with persistent lesions at a second renal biopsy after induction therapy, there was better renal 10-year survival with IV-S lesions (63.6%) versus those with IV-G lesions (0%) (23). Furthermore, the IV-S biopsies had fewer immune deposits with more fibrinoid necrosis compared with IV-G. Other studies have also reported no significant difference in the outcome of IV-S and IV-G LN classes (11,24,25). In a study of 92 patients with LN who were reclassified according to the ISN/RPS 2003 criteria, renal function was more likely to deteriorate in IV-G than in IV-S patients.…”
Section: Does the Isn/rps Classification Help Prognosticate Outcome?mentioning
confidence: 80%